Psychiatry of Parkinson's Disease (Karger, 2012)
Psychiatric symptoms are common in the neurological and geriatric care of patients with Parkinson’s disease. This book assembles short reviews from experts in the field to chart the various psychiatric syndromes known in Parkinson’s disease, their presentation, etiology and management. Presented are special topics on epidemiology of psychiatric symptoms, affective disorders and apathy, early cognitive impairment through to dementia, visuoperceptual dysfunction, psychotic disorders, sleep disturbances, impulse disorders and sexual problems. Further, rarely discussed issues, such as the relationship between somatoform disorders and parkinsonism are reviewed. This publication is essential reading for old age psychiatrists, gerontologists and neurologists who work with patients suffering from Parkinson’s disease.